PERENCANAAN MESIN PENGUPAS SERABUT KELAPA DARI TEMPURUNG BERKAPASITAS 12 BIJI/JAM - Dicky Djohari; Ninuk Jonoadji (Petra Christian University, 2013)
Coconut plant is one plant that all of the parts can be used for everyday life. One partthat can beused iscoconut fiber. Coconut fiber can be used for mats, equipment of dishwasher, and filling the car seat.The design of this machine is used to efficient the time, which is usually the process of decomposition of coconut shell fibers take a long time to 15 minutes. By making this machine can shorten the time and the maximum yield of coconut fiber which is free from fibers of coconut shells. consumers need a clean shell of coconut fibers and need much fibers.The result of this reasearch supports that the profits who obtained more a lot as compare with its cost of production. the machine can work 8 hours per day with a yield 96 pieces